RNAi-dependent expression of sperm genes in ADL chemosensory neurons is required for olfactory responses in Caenorhabditis elegans - Ow, Maria C.; Nishiguchi, Mailyn A.; Dar, Abdul Rouf; Butcher, Rebecca A.; Hall, Sarah E. (Frontiers in Molecular Biosciences, 2024)
Environmental conditions experienced early in the life of an animal can result in gene expression changes later in its life history. We have previously shown that C. elegans animals that experienced the developmentally arrested and stress resistant dauer stage (postdauers) retain a cellular memory of early-life stress that manifests during adulthood as genome-wide changes in gene expression, chromatin states, and altered life history traits. One consequence of developmental reprogramming in C. elegans postdauer adults is the downregulation of osm-9 TRPV channel gene expression in the ADL chemosensory neurons resulting in reduced avoidance to a pheromone component, ascr#3. This altered response to ascr#3 requires the principal effector of the somatic nuclear RNAi pathway, the Argonaute (AGO) NRDE-3. To investigate the role of the somatic nuclear RNAi pathway in regulating the developmental reprogramming of ADL due to early-life stress, we profiled the mRNA transcriptome of control and postdauer ADL in wild-type and nrde-3 mutant adults. We found 711 differentially expressed (DE) genes between control and postdauer ADL neurons, 90% of which are dependent upon NRDE-3. Additionally, we identified a conserved sequence that is enriched in the upstream regulatory sequences of the NRDE-3-dependent differentially expressed genes. Surprisingly, 214 of the ADL DE genes are considered “germline-expressed”, including 21 genes encoding the Major Sperm Proteins and two genes encoding the sperm-specific PP1 phosphatases, GSP-3 and GSP-4. Loss of function mutations in gsp-3 resulted in both aberrant avoidance and attraction behaviors. We also show that an AGO pseudogene, Y49F6A.1 (wago-11), is expressed in ADL and is required for ascr#3 avoidance. Overall, our results suggest that small RNAs and reproductive genes program the ADL mRNA transcriptome during their developmental history and highlight a nexus between neuronal and reproductive networks in calibrating animal neuroplasticity.